Comparison of Maternal and Fetal Outcomes in Induction of Labor Using Misoprostol Versus Foley’s Catheter in Term Pregnancies - Asifa Majid, Azra Rashid, Afshin Aman, Saima Noreen, Anikah Kanwal, Tahira Akhtar, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: The induction of labor is a widely practiced obstetric intervention when continuation of pregnancy poses greater risks than delivery. Various methods are used for cervical ripening, with misoprostol and Foley’s catheter being among the most common. Objectives: To compare maternal and fetal outcomes in induction of labor using misoprostol versus Foley’s catheter in term pregnancies. Study Design & Setting: A randomized controlled trial was conducted at the Department of Obstetrics and Gynecology Jinnah Hospital, Lahore. Methodology: A total of 120 term pregnant women requiring induction were randomly allocated into two groups: Misoprostol group (n = 60) and Foley’s catheter group (n = 60). Baseline demographics, Bishop scores, and indications for induction were recorded. Misoprostol 25 µg was administered vaginally at 4-hour intervals up to a maximum of 6 doses, while a 16–18 French Foley’s catheter balloon was inserted in the comparator group. Primary outcomes were induction-to-delivery interval and mode of delivery. Secondary outcomes included need for oxytocin augmentation, maternal complications, neonatal Apgar scores, NICU admissions, and perinatal mortality. Data were analyzed using SPSS version 25, with p < 0.05 considered significant. Results: The mean induction-to-delivery interval was significantly shorter in the Misoprostol group (9.6 ± 3.1 hours) compared to the Foley’s catheter group (12.4 ± 3.8 hours, p < 0.001). Vaginal delivery occurred more frequently with misoprostol (80.0% vs. 63.3%), while cesarean section was higher in the Foley’s group (36.7% vs. 20.0%, p = 0.048). Maternal and neonatal complications were comparable between groups. Conclusion: Misoprostol demonstrated superior efficacy in achieving shorter induction-to-delivery interval and higher vaginal delivery rates compared to Foley’s catheter, with similar safety profiles. Keywords: Cesarean section, Foley’s catheter, Induction of labor, Misoprostol, Neonatal outcome, Vaginal delivery